Chemical Composition, Optical Properties and Sources of PM2.5 From a Highly Urbanized Region in Northeastern Mexico - Acuña Askar, Karim; González, Lucy T.; Mendoza, Alberto; Kharissova, Oxana V.; Rodríguez-Garza, Andrea; Lara, Eleazar M.; Campos, Alfredo; López-Serna, D.; Bautista-Carrillo, Lilia M.; Alfaro-Barbosa, J. M.; Longoria-Rodríguez, F. E. (Frontiers in Environmental Science, 2022)
Here, we report the chemical composition and optical properties of the fine particles (PM2.5) and water-soluble organic carbon (WSOC) of these particles. Additionally, the potential sources of WSOC emission were determined through the study on fluorescence excitation–emission matrix spectra and parallel factor analysis (EEM-PARAFAC). Samples were collected in an urban site of the Monterrey Metropolitan Area in Mexico during summer and winter and characterized using attenuated total reflectance-Fourier-transform infrared spectroscopy (ATR-FTIR), ultraviolet-visible-near infrared-diffuse reflectance spectroscopy (UV–Vis-NIR-DRS), fluorescence spectroscopy, X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD) techniques. The ATR-FTIR analyses allowed the identification of inorganic ions (e.g., CO32−, SO42−, NO3−), organic functional groups [e.g., carbonyls (C=O), organic hydroxyl (C-OH), carboxylic acid (COOH)], and aromatic and unsaturated aliphatic hydrocarbons. The results obtained by XRD, and XPS revealed the presence of organic and inorganic chemical species in PM2.5. The diffuse reflectance spectra of PM2.5 provided the absorption bands in the UV region for CaSO4, CaCO3, and aluminosilicates. The absorption coefficient at 365 nm (Abs365) and Ångström absorption exponent (AAE) values obtained for the aqueous extracts suggest that many of the water-soluble organic compounds corresponded to brown carbon (BrC) chromophores. The mass absorption efficiency values at 365 nm (MAE365) were higher in the winter than summer samples, suggesting the presence of more BrC compounds in the winter samples. The fluorescence indices combined with EEM-PARAFAC analysis showed that the WSOC fraction was mainly composed of humic-like substances (HULIS) which are both of terrestrial and microbial origin.